Campylobacter jejuni Serine Protease HtrA Cleaves the Tight Junction Component Claudin-8 - Sharafutdinov, Irshad; Esmaeili, Delara Soltan; Harrer, Aileen; Tegtmeyer, Nicole; Sticht, Heinrich; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2020)
Campylobacter jejuni express the high temperature requirement protein A (HtrA), a secreted serine protease, which is implicated in virulence properties of the pathogen. Previous studies have shown that C. jejuni HtrA can cleave the epithelial transmembrane proteins occludin and E-cadherin in the tight and adherens junctions, respectively. In the present report, we studied the interaction of HtrA with another human tight junction protein, claudin-8. Confocal immunofluorescence experiments have shown that C. jejuni infection of the intestinal polarized epithelial cells in vitro leads to a relocation of claudin-8. Wild-type C. jejuni induced the downregulation of claudin-8 signals in the tight junctions and an accumulation of claudin-8 agglomerates in the cytoplasm, which were not seen during infection with isogenic ΔhtrA knockout deletion or protease-inactive S197A point mutants. Western blotting of protein samples from infected vs. uninfected cells revealed that an 18-kDa carboxy-terminal fragment is cleaved-off from the 26-kDa full-length claudin-8 protein, but not during infection with the isogenic ΔhtrA mutant. These results were confirmed by in vitro cleavage assays using the purified recombinant C. jejuni HtrA and human claudin-8 proteins. Recombinant HtrA cleaved purified claudin-8 in vitro giving rise to the same 18-kDa sized carboxy-terminal cleavage product. Mapping studies revealed that HtrA cleavage occurs in the first extracellular loop of claudin-8. Three-dimensional modeling of the claudin-8 structure identified an exposed HtrA cleavage site between the amino acids alanine 58 and asparagine 59, which is in well agreement with the mapping studies. Taken together, HtrA operates as a secreted virulence factor targeting multiple proteins both in the tight and adherens junctions. This strategy may help the bacteria to open the cell-to-cell junctions, and to transmigrate across the intestinal epithelium by a paracellular mechanism and establish an acute infection.